Legal Protection for Victims of Domestic Violence from a Victimological Perspective (A Study of Decision No. 661/PID.SUS/2023/PN SMN) - Tryveni Anauli Simanjuntak; Ghina Salsabila Aven (LEGAL BRIEF, 2026)
Domestic violence remains a critical issue in Indonesia despite comprehensive legal frameworks established through Law Number 23 of 2004 on the Elimination of Domestic Violence. This study examines the legal protection afforded to victims of domestic violence from a victimological perspective, with a focus on Decision Number 661/Pid.Sus/2023/PN Smn. The research employs a normative legal approach, utilizing statutory analysis and case study methodology to evaluate the implementation of victim protection principles in judicial practice. Primary legal materials include relevant legislation and the court decision, analyzed through descriptive qualitative methods within a victimological framework. The findings reveal significant gaps between normative standards and practical implementation. While the legal framework comprehensively regulates victim rights including protection, restitution, and recovery, the examined court decision demonstrates fundamental deficiencies: absence of restitution orders, lack of protection orders to prevent repeat victimization, imposition of a suspended sentence that inadequately deters recidivism, and insufficient consideration of victims' psychological and economic vulnerabilities. The decision prioritizes the perpetrator's interests over victim protection, neglecting structural inequalities and power imbalances inherent in domestic violence cases. This study concludes that judicial practice requires substantial reform to fully integrate victimological principles, ensuring victims receive comprehensive protection, justice, and recovery while preventing secondary victimization.